PLACE OF THE NATIONAL GUARD OF UKRAINE IN THE TASK TO CURB ILLEGAL ACTIONS OF THE GROUP OF PRISONERS IN PENAL INSTITUTIONS - Petik, А. V. (Honor and Law, 2019)
The analysis of situations, connected with occasions happened in correctional institutions and units reacting on such occasions were made. The role of the National Guard of Ukraine among the organizations involved to stopping of mass illegal actions of prisoners in correctional institutions was determined. The legislative acts of Ukraine determined forces and means needed to react on crisis situations in correctional institutions were analyzed